Atypical Presentation of Spindle Cell Carcinoma - Harshika Singh; Sachin Khanduri; Anvit Krishnam; Poonam Yadav; Harleen Chawla (Journal of Clinical and Diagnostic Research, 2021)
Spindle Cell Carcinoma (SCC) of the lung is a rare entity. Computed Tomography (CT) and histopathology forms the basis of diagnosis. Here, authors presented a case of a 30-year-old male patient who reported with complaints of painless abdominal swelling associated with shortness of breath and fever. The patient underwent Contrast Enhanced CT (CECT) of chest, abdomen and pelvis with percutaneous CT guided biopsy. The final diagnosis was SCC of lung with transdiaphragmatic spread to abdomen. This case is clinically significant as it depicts unusual spread of SCC presenting as thoracoabdominal mass.